Adaptation from a Paper-Based Nephron Manipulative to a Hands-On Electronic Format to Teach Renal Physiology, Pathophysiology, and Pharmacology - Haymete, Maedot Ariaya; Contaifer, Daniel; Evans, Ryan; Carvalho, Helena (Advances in physiology education, 2025)
The complex processes of electrolytes transport across the nephron often pose learning challenges for medical students. Manipulatives are a means of providing an interactive learning experience that increases understanding and content retention. In this study we updated our previous in-person, paper-based nephron manipulative into a digital, interactive PowerPoint format while also integrating clinical applications. Twenty first-year medical students completed a pre-manipulative quiz (pre-test) and then participated in the manipulative intervention where they electronically dragged and positioned electrolytes/molecules onto corresponding transporters within each PowerPoint slide depicting specific nephron segments. Participants completed a post-manipulative quiz (post-test) and participated in a faculty-based discussion in that same session. A long-term knowledge assessment quiz (long-term test) was administered nine months later in their second year of medical school. A non-intervention group, consisting of 26 second-year medical students that did not participate in the nephron manipulative as first-year students, provided a comparison for the natural learning progression without the manipulative intervention. A statistically significant improvement was observed from pre-test to post-test (p = 0.0093), confirming that the manipulative intervention produced a meaningful improvement in student learning in the short term. When comparing learning outcomes by question subject, Pharmacology questions showed higher average gain (+0.13) compared to Physiology (+0.07), with less knowledge decay over time (–0.03 vs –0.09). Student feedback was overwhelmingly positive. This electronic manipulative demonstrated success in interactive teaching of nephron physiology and pathophysiology concepts and is a valuable teaching tool due to its customizable design, available at free to lost cost.